Kenneth M. Setton, Catalan domination of Athens, 1311-1388. The Mediaeval Academy of America, Cambridge, Mass., 1948. xv + 323 págs. + 8 láms. - D'Olwer, Luis Nicolau (El Colegio de México, 1949)
Se reseñó el libro: Catalan domination of Athens, 1311-1388.